Aproveitamento de resíduos agroindistriais de pimenta para elaboração de geleia diet - Sora, Gisele Teixeira de Souza (2011)
This study aimed to the preparation and characterization of diet pepper jam based on waste and leftover "dedo-de-moça" pepper (Capsicum baccatum var. pendulum) provided by Taste of Village Agrobusiness located in Atalaia -Paraná, giving these products a noblest destination and increasing their commercial value. The jam was characterized by physical-chemical and microbiological analysis besides sensory testing. This complete evaluation showed satisfactory results when compared to results found by other authors and permitted by Brazilian legislation. It found a product free from any microbiological contamination, with the physical-chemical standards within the limits allowed by ANVISA, excellent acceptance by panelists in sensory analysis and great score on consumer acceptance test. Rheological behavior evaluation was performed for the diet pepper jam, and viscosity data were adjusted to the Arrhenius model to obtain the activation energy. The diet pepper jam showed a pseudoplastic behavior at all temperatures tested ranged from 10° - 60° C, and the values were well fitted by the Power Law model. The activation energy obtained by the Arrhenius equation, 30 s-1, was 10.35 kJmol-1. The verification of phenolic compounds present in both pepper jam and fresh pepper samples were performed by the colorimetric method of Folin-Ciocalteau and the quantification and evaluation of their antioxidant activity were analyzed by the DPPH free radical system. A variety of phenolic compounds was observed in the samples. It was noted that due to cooking, the percentage of antioxidant activity (AA%) for jam was slightly lower than in natura pepper percentage. Fresh pepper showed six times more protection to oxidation (approximately 88,6 %AA) compared with the jelly (approximately 36,23 %AA).